Everything soccer - Hoena, B. A.; Gonzalez, Omar, 1988-; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 2014)
A browseable introduction to the world's most popular team sport featuring information about history, famous players, rules, lingo, equipment, and more, with over 100 pictures and an interactive glossary.
Seriously soccer -- Get in the game -- Gear, games, and grandstands -- Fun with soccer.
Includes bibliographical references (page 62) and index.
Keywords: Soccer -- Juvenile literature; Soccer